Environmental changes in the Ulan Buh Desert, southern Inner Mongolia, China since the middle Pleistocene based on sedimentology, chronology and proxy indexes. (15th November 2015) - Li, Guoqiang; Jin, Ming; Chen, Xuemei; Wen, Lijuan; Zhang, Jiawu; Madsen, David; Zhao, Hui; Wang, Xin; Fan, Tianlai; Duan, Yanwu; Liu, Xiaokang; Wu, Duo; et al.
Abstract: The Ulan Buh Desert (UBD), in southwestern Inner Mongolia, is one of the main dune fields and dust source areas in northern China. The formation of the desert and associated environmental changes since the middle Pleistocene are still unclear due to a lack of depositional records and environmental proxy index analyses. In this study, quartz and K-feldspar optical dating, environmental proxy indexes of grain size, loss on ignition, pollen, and ostracod analysis were employed to supplement the sediment record of a 120.5 m drill core, WL12ZK-1, from the southern UBD. In combination with previous stratigraphic records obtained from drill cores WL10ZK-1 (35 m deep) and WL10ZK-2 (32 m deep) from the northern UBD, and drill core WL12ZK-2 (80 m deep) from the northeastern UBD, these proxies indicate there has been essentially an arid environment in the UBD, with desert or steppe vegetation, since the middle Pleistocene, and that sand dunes were widely distributed in the UBD beginning at least ∼230 ka ago. The Yellow River filled a freshwater paleolake beginning ∼15 ka ago that covered both the UBD and the adjacent Hetao Plain. The paleolake lasted until ∼87 ka, and was associated with wetlands along its margins. Steppe vegetation was present in the surrounding region. An arid environment appeared again after ∼87 ka, and there is no evidence of a large stable lake in the UBD at any time thereafter. Sand dune deposition and a very arid desert environment were present throughout the last glacial period and lasted into the early Holocene. During the Holocene these arid conditions were interrupted by minor wetland intervals. Deserts in southern Inner Mongolia formed at least since the middle Pleistocene, expanded during the last glaciation and into the early Holocene and again after ∼2 ka. We suggest that a combination of tectonic activity and climate change may be responsible for desert formation and environmental changes in southern Inner Mongolia since the middle Pleistocene, with additional human influence exacerbating these conditions in the late Holocene. Highlights: Drill cores in the UBD have recovered eolian sand/lake alternations since the Pleistocene. Aridity started before ∼230 ka and desert vegetation prevailed until the present. A paleolake environment occurred within the desert between ∼155 ka and ∼90 ka. Deserts expanded during the Last Glacial to early Holocene and after 2 ka in southern Mongolia. Tectonic activity, climate change and human activity may be responsible for this sequence.